2020
DOI: 10.1007/s40267-020-00757-3
|View full text |Cite
|
Sign up to set email alerts
|

Paradigm shift of drug information centers during the COVID-19 pandemic

Abstract: The novel coronavirus disease 2019 (COVID-19) pandemic is a major global threat affecting millions of lives throughout the world physically and psychologically. With the asymptomatic presentation of COVID-19 in many patients and the similarity of its symptoms with the common cold and influenza, the need for accurate information on the disease is very important for its identification and proper management. Accurate information on the disease, its prevention and treatment can be disseminated through drug informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
(29 reference statements)
1
14
1
2
Order By: Relevance
“…The immune-suppression effect of dexamethasone is not clear in our finding, because the result of immune response to vaccines recorded insignificant different among the groups of the experiment. These finding is not agreed with [20] who reported that the induction of immunosuppression by dexamethasone in ducks result in progressively declining antibodies titers to very low levels which may make the birds susceptible to infection by challenge viruses, which lead to clinical disease and virus shedding. These differences in finding may be due to the time course of treatment.…”
Section: Discussioncontrasting
confidence: 78%
“…The immune-suppression effect of dexamethasone is not clear in our finding, because the result of immune response to vaccines recorded insignificant different among the groups of the experiment. These finding is not agreed with [20] who reported that the induction of immunosuppression by dexamethasone in ducks result in progressively declining antibodies titers to very low levels which may make the birds susceptible to infection by challenge viruses, which lead to clinical disease and virus shedding. These differences in finding may be due to the time course of treatment.…”
Section: Discussioncontrasting
confidence: 78%
“…Exposure to negative information about the vaccines was associated with a high level of vaccine hesitancy in Philippines [ 47 ]. There is the need for accurate information on the COVID-19 vaccine, which is very important for its proper management [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CPPs can liaise with drug information centres, national health authorities and organizations to improve the use of information services provided by them. 20 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CPPs can liaise with drug information centres, national health authorities and organizations to improve the use of information services provided by them. 20,39 Ministry of Health and Population Nepal (MOHP) 40 is also posting COVID-19 occurrence updates and resource materials. Similarly, WHO is providing situation reports regarding COVID-19 for the public, doctors and healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation